Estimation of medical equipment prices – a case study of tomotherapy equipment in the Czech Republic - Donin, Gleb; Barták, Miroslav; Kneppo, Peter (Journal of Business Economics and Management, 2017)
Medical equipment (ME) is often considered to be an important factor in the growth of healthcare expenditures. In the Czech Republic (CR) validated approach does not yet exist for hospitals to use to assess commercial offers, nor is there a generally accepted methodology for regulatory bodies to allow for the evaluation of the effectiveness of prior purchases. This study intends to present a methodological approach that will allow for assessing the effectiveness of the procurement of capital ME based on international prices. The case of the purchase of tomotherapy system in the CR was used to demonstrate the developed approach. We performed a multiway search for international estimated and exact prices for tomotherapy unit using public-procurement databases, scientific papers, health technology assessment studies, professional reports, and Internet searches. All of the data that was gathered on prices was subjected to critical assessment vis-à-vis the reliability of the information. This research lays new methodology that may provide general background of international comparison studies focused on ME. The results provide support for decision making about the acquisitions of ME.